Study of zircon U–Pb chronology, tectonic environment and stratigraphic attribution of mafic metavolcanic rocks in the Xiaohuangshan area, Beishan, Inner Mongolia - Xinzhuo Hu; Guanghao Tian; Jiyuan Yang; Wen Deng (Discover Applied Sciences)
Abstract Meta basic volcanic rocks were occupied the Xiaohuangshan area, Beishan, Inner Mongolia. Previous studies on the formation age and tectonic environment of this set of strata had less data, and opinions on the attribution of this set of strata were not unified. This research investigated the rock association, isotope chronology and petrogeochemical characteristics. Zircon U–Pb dating data were concentrated in the 416-443 Ma and 440-474 Ma intervals. The characteristics of petrology and petrochemistry showed that the original rock was a set of basic volcanic rocks dominated by basalt. The REE distribution pattern was generally gentle, with weak positive Eu anomaly, which was consistent with basic igneous rock. Rb/Sr ratio (0.03–0.08) indicated that the material source was mainly from the upper mantle.τ (6.62–30.55) suggested that the rock belonged to volcanic rocks of orogenic belt. Alkalinity rate (1.16–1.60) and related graphical discrimination revealed that it had the characteristics of island arc volcanic rocks. The eruption age of basic volcanic rocks in the study area was the Middle Ordovician, and the magma mainly originated from the upper mantle and formed in the island arc tectonic environment. Based on the comprehensive analysis of lithology association, age, tectonic environment and tectonic position, this set of strata was erupted into the Ordovician—Silurian Gongpoquan Formation.